Effects of hyperbilirubinemia on markers of genotoxicity and total oxidant and antioxidant status in newborns. (2nd January 2022) - Bulut, Ozgul; Erek, Aybala; Duruyen, Sadettin
Abstract: Hyperbilirubinemia is one of the most common diseases in neonates. Slight elevations in bilirubin levels exert antioxidant effects but high levels may cause oxidative damage in newborns. We assessed the effects of hyperbilirubinemia on DNA damage and total oxidant and antioxidant status in newborns receiving phototherapy. A total of 68 term newborn infants exhibiting idiopathic unconjugated hyperbilirubinemia (UCH) requiring phototherapy and 27 age-matched healthy controls were enrolled in the study. Plasma 8-hydroxy-2 deoxy-guanosine (8-OH-dG) levels, total oxidant status (TOS), and total antioxidant status (TAS) were compared between newborns with UCH requiring phototherapy and age-matched healthy controls. The extent of DNA damage, the TOS, and the TAS were significantly higher in the study group than the control group ( p  < 0.01). The extent of DNA damage and the TOS increased at lower bilirubin levels; this became significant at bilirubin levels >16 mg/dL. A significant increase in TAS was observed even at low bilirubin levels, and the TAS was positively correlated with the bilirubin level to 30 mg/dL. At slightly elevated levels bilirubin serves as a physiological antioxidant. However, the high bilirubin levels evident in the present study increased DNA damage and oxidative stress.